Assessment of ecological damage from the NATO bombing of the Republic of Serbia in 1999 - Bakrač Saša T.; Klem Emilija; Milanović Miško (Војно дело, 2018)
In 1999, NATO bombed the Republic of Serbia, which inflicted irreparable environmental damage on ecosystems and habitats. The topic of this paper is the method of determining and analyzing the assessment of inflicted ecological damage. Its quantification is possible, but it requires an integrated approach, since the exact value can be estimated only on a case-by-case basis. The financial valorization of environmental damage is an open and complex issue and it implies moral and ethical parameters. The paper presents in general the assessment of ecological damage, and also the assessment of the damage inflicted on endemic and other types of habitats and ecosystems. A special emphasis is paid on the environmental damage assessment and the assessment of human health consequences that have arisen from the use of munitions with depleted uranium. The problem of determining ecological damage and its consequences for ecosystems, habitats and humans due to the NATO bombing of Serbia in 1999 is particularly pointed out.